2016
DOI: 10.1016/j.heares.2015.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal development of wideband reflectance tympanometry in normal and at-risk infants

Abstract: Purpose The goals of this study were to measure normal characteristics of ambient and tympanometric wideband acoustic reflectance, which was parameterized by absorbance and group delay, in newborns cared for in well-baby and Neonatal Intensive Care Unit (NICU) nurseries, and to characterize the normal development of reflectance over the first year after birth in a group of infants with clinically normal hearing status followed longitudinally from birth to one year of age. Methods Infants were recruited from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
56
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(74 citation statements)
references
References 42 publications
11
56
1
6
Order By: Relevance
“…Overall, these studies demonstrated that the mean absorbance is higher in neonates and young infants up to 6 months of age compared to young adults across the frequency range. Among infants, one-month-old infants showed higher absorbance compared to newborns and older infants (Hunter et al, 2015). The high absorbance in frequencies below 1000 Hz in young infants is conjectured to be due to power loss from flaccid ear canal movement (Keefe et al, 1993).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…Overall, these studies demonstrated that the mean absorbance is higher in neonates and young infants up to 6 months of age compared to young adults across the frequency range. Among infants, one-month-old infants showed higher absorbance compared to newborns and older infants (Hunter et al, 2015). The high absorbance in frequencies below 1000 Hz in young infants is conjectured to be due to power loss from flaccid ear canal movement (Keefe et al, 1993).…”
Section: Introductionmentioning
confidence: 88%
“…Sound transmission through the middle ear undergoes developmental changes throughout infancy (Hunter et al, 2015; Keefe and Levi, 1996; Keefe et al, 1993; Sanford and Feeney, 2008; Werner et al, 2010) and continues into childhood (Beers et al, 2010; Hunter et al, 2008; Okabe et al., 1988; Wang et al, 2016). Maturation of the middle ear transmission has important implications for perceptual and physiologic studies of auditory development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, an absorbance test held in nonpressurized conditions will be useful for monitoring middle ear state immediately after surgery, with perforated eardrum during neonatal hearing screening. In several studies performed in ambient pressure proved to be able to detect changes in middle ear function significantly for infants and neonatal measurements [23,24]. In the case of patients with ventilation tubes in the eardrum, data from Groon et al [25], suggest that: (i) for any leak larger than 0.25 mm there are absorbance alteration effects up to 10 kHz; (ii) above 1 kHz these effects are unpredictable; and (iii) absorbance values were mostly increased in the lower frequency bands (0.1-0.2 and 0.2-0.5 kHz).…”
Section: Absorbance and Related Measurementsmentioning
confidence: 99%